Muscarinic Receptors Types 1 and 2 in the Preoptic-Anterior Hypothalamic Areas Regulate Ovulation Unequally in the Rat Oestrous Cycle - Yadira L. López-Ramírez; Kayro López-Ramírez; Isabel Arrieta-Cruz; Angélica Flores; Luciano Mendoza-Garcés; Raúl A. Librado-Osorio; Roger Gutiérrez-Juárez; Roberto Domínguez; María Esther Cruz (International Journal of Endocrinology)
Muscarinic receptors types 1 (m1AChR) and 2 (m2AChR) in the preoptic and anterior hypothalamus areas (POA-AHA) were counted, and the effects of blocking these receptors on spontaneous ovulation were analysed throughout the rat oestrous cycle. Rats in each phase of the oestrous cycle were assigned to the following experiments: (1) an immunohistochemical study of the number of cells expressing m1AChR or m2AChR in the POA-AHA and (2) analysis of the effects of the unilateral blockade of the m1AChR (pirenzepine, PZP) or m2AChR (methoctramine, MTC) on either side of the POA-AHA on the ovulation rate. The number of m2AChR-immunoreactive cells was significantly higher at 09:00 h on each day of the oestrous cycle in the POA-AHA region, while no changes in the expression profile of m1AChR protein were observed. The ovulation rate in rats treated with PZP on the oestrous day was lower than that in the vehicle group. Animals treated on dioestrous-1 with PZP or MTC had a higher ovulation rate than those in the vehicle group. In contrast, on dioestrous-2, the MTC treatment decreased the ovulation rate. These results suggest that m1AChR or m2AChR in the POA-AHA could participate in the regulation of spontaneous ovulation in rats.